Poetics of Abjection: Mapping Homo Sacerin Usha Ganguli’s Rudali (SCHOLARS: Journal of Arts & Humanities, 2026)
This article reads Usha Ganguli’s Rudali, a dramatic adaptation of Mahasweta Devi’s novella with the same title, to examine the precarious socio-political condition of rudalis, the Dalit women hired to mourn the death of rich people. Their abject lives resonate with Giorgio Agamben’s idea of homo sacer, figures stripped of civil rights, social recognition, and human dignity. To show the intersectionality of class, caste, and gender, this article makes a close textual reading of dialogue, characterization, and stage design.  It also investigates how the ritualized mourning spectacle augments the recognition of rudalis who are otherwise excluded from the socio-political realm, and why Ganguli recasts them as agents of political resistance in postcolonial India. Drawing on Julia Kristeva’s concept of abjection, understood as social disgust and exclusion, and Agamben’s notion of homo sacer, the article explores how caste, class, and gender-based expulsion relegate Sanichari and her rudali community to bare existence, rendering them expendable within the hierarchized socio-economic structures. It argues that ritualized mourning becomes a counter-discursive practice through which rudali community expresses their dissent and resist social abjection. Therefore, the charting of their grief as a public performative act, Ganguli’s rework transforms the culturally silenced rudali homo sacer into a speaking subaltern whose mourning mediates to expose systemic injustice. Finally, the play, as a cautionary poetics of resistance, stages the ransacked lives of marginalized rudalis while critiquing the uneven social order. These findings serve to broader questions of intersectional injustice and the politics of visibility confronting marginalized communities.